What makes a good therapist? - Manning, Walt (Henry Stewart Talks, 2017)
Personal characteristics of the clinician, The medical vs. the common factors model, The importance of the therapeutic alliance, The development of clinical expertise, The unique characteristics of experts, Decision making with rules and principles, Brief perspectives about the therapeutic process, Four principles of therapeutic change